Identification and characterization of a tRNA decoding the rare AUA codon in Haloarcula marismortui - Köhrer, Caroline (Cold Spring Harbor Laboratory Press, 2008)

(untitled)
Annotation of the complete genome of the extreme halophilic archaeon Haloarcula marismortui does not include a tRNA for translation of AUA, the rare codon for isoleucine. This is a situation typical for most archaeal genomes sequenced to date. Based on computational analysis, it has been proposed recently that a single intron-containing tRNA gene produces two very similar but functionally different tRNAs by means of alternative splicing; a UGG-decoding tRNA(Trp) (CCA) and an AUA-decoding tRNA(Ile) (UAU). Through analysis of tRNAs from H. marismortui, we have confirmed the presence of tRNA(Trp) (CCA), but found no evidence for the presence of tRNA(Ile) (UAU). Instead, we have shown that a tRNA, currently annotated as elongator methionine tRNA and containing CAU as the anticodon, is aminoacylated with isoleucine in vivo and that this tRNA represents the missing isoleucine tRNA. Interestingly, this tRNA carries a base modification of C34 in the anticodon different from the well-known lysidine found in eubacteria, which switches the amino acid identity of the tRNA from methionine to isoleucine and its decoding specificity from AUG to AUA. The methods described in this work for the identification of individual tRNAs present in H. marismortui provide the tools necessary for experimentally confirming the presence of any tRNA in a cell and, thereby, to test computational predictions of tRNA genes.